The evaluating performance of commercial banks using CAMEL model application to Bahraini banks during the period (2013-2020) - Saied, Mohamad; Yahia, Salem (Journal of Pure & Applied Sciences, 2022)
The purpose of this research is to examine the financial performance of sample of Bahrain commercial banks using the "CAMEL" model  in order to indentify the bank’ strength and weaknesses .The  annual financial reports of the Bahraini banks are used to obtain data related to some important ratios to evaluate the banks’ performance. The study methodology used an analytical approach during the period 2013-2020 to identify strengths and weaknesses.  Among the most important results that were reached is that number of classified strong financial performance banks were represented by one bank only, which is (the Gulf Bank), while the unsatisfactory financial performance banks were represented by the (United Bank), while the rest of the banks were considered reasonable financial performance banks. In light of the results of the study, we recommend working to compel banks to review the performance levels of their financial and banking operations by applying the elements of the banking assessment model on a continuous basis, monitoring the situation of banks in trouble by following the trend of financial ratios that reflect capital solvency ratios, the ability to pay and the efficiency of the administration in operating available assets, working on developing the mechanisms for applying the components of the CAMEL assessment model.